2018
DOI: 10.1371/journal.ppat.1007236
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of the SARS coronavirus spike glycoprotein in complex with its host cell receptor ACE2

Abstract: The trimeric SARS coronavirus (SARS-CoV) surface spike (S) glycoprotein consisting of three S1-S2 heterodimers binds the cellular receptor angiotensin-converting enzyme 2 (ACE2) and mediates fusion of the viral and cellular membranes through a pre- to postfusion conformation transition. Here, we report the structure of the SARS-CoV S glycoprotein in complex with its host cell receptor ACE2 revealed by cryo-electron microscopy (cryo-EM). The complex structure shows that only one receptor-binding domain of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
967
4
14

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 854 publications
(1,017 citation statements)
references
References 38 publications
32
967
4
14
Order By: Relevance
“…Recent structural work comparing recombinant S proteins from SARS-CoV and MERS-CoV in isolation and in complex with their cognate receptors or neutralizing antibodies suggested an activation mechanism for coronavirus fusion (Gui et al, 2017;Kirchdoerfer et al, 2018; Song et al, 2018;Walls et al, 2019;Yuan et al, 2017). Specifically, SARS-CoV and MERS-CoV S structures in complex with neutralizing antibodies isolated from survivors showed both antibodies competitively blocked receptor interaction, in agreement with previous surface plasmon resonance data (Corti et al, 2015;Rockx et al, 2008;Traggiai et al, 2004;Walls et al, 2019).…”
Section: Mechanism Of Fusion Activationsupporting
confidence: 78%
See 3 more Smart Citations
“…Recent structural work comparing recombinant S proteins from SARS-CoV and MERS-CoV in isolation and in complex with their cognate receptors or neutralizing antibodies suggested an activation mechanism for coronavirus fusion (Gui et al, 2017;Kirchdoerfer et al, 2018; Song et al, 2018;Walls et al, 2019;Yuan et al, 2017). Specifically, SARS-CoV and MERS-CoV S structures in complex with neutralizing antibodies isolated from survivors showed both antibodies competitively blocked receptor interaction, in agreement with previous surface plasmon resonance data (Corti et al, 2015;Rockx et al, 2008;Traggiai et al, 2004;Walls et al, 2019).…”
Section: Mechanism Of Fusion Activationsupporting
confidence: 78%
“…Free 9-O-Ac-Sia, however, did not trigger S conformational changes associated with membrane fusion . This observation contrasts with data for SARS-CoV S, for which addition of the human angiotensin-converting enzyme 2 (ACE2) ectodomain (the proteinaceous receptor) promoted S refolding to the postfusion state (Song et al, 2018;Walls et al, 2019). These findings suggested that either 9-O-Ac-Sia-containing receptors differ from proteinaceous receptors in their mode of action, or that an interaction with a yet unidentified proteinaceous receptor is required before or after virus internalization for HCoV-OC43 entry into target cells.…”
Section: Diversity Of Cov Receptors and Entry Mechanismscontrasting
confidence: 76%
See 2 more Smart Citations
“…Since binding of ACE2 to the isolated B domain was Figure S3 and Tables S4 and S5. reported to have an equilibrium dissociation constant (K D ) in the nanomolar range (Li et al, 2005c), one would expect that full saturation should occur rapidly in the conditions of our experiments (100-fold concentration excess over the K D ). Previous reports, however, suggested a lower affinity of the fulllength S trimer, relative to the isolated B domain, for ACE2 (Kirchdoerfer et al, 2018;Matsuyama and Taguchi, 2009;Song et al, 2018). We propose that the conformational landscape of the B domains in the context of the SARS-CoV S trimer, sampling open and closed conformations, decreases the apparent binding affinity for ACE2 and S230 due to masking of their binding sites in the closed state.…”
Section: Activation Mechanism Of Coronavirus Membrane Fusionmentioning
confidence: 57%